mDia1 senses both force and torque during F-actin filament polymerization - Miao Yu (Nature Portfolio, 2017)
Formins are actin-polymerisation factors that are sensitive to force. Here the authors find that pulling force on an actin filament promoted faster actin polymerisation by the formin mDia1, and also found that the actin filament must be torsionally unconstrained, suggesting that mDia1 can also sense torque.